“En avant” : le mot‑clé d’un champion olympique comme instrument psychologique pour l’action sportive - Arnaud Laurin-Landry; Maryvonne Merri (Activités)
In this article, we put into action a new conceptualization of self-talk using the methods of analysis developed in a previous article. To this end, we analyze the cue word “En Avant” (forward) that William, an Olympic mogul-skiing champion, says to himself when he does a double twisting backflip on the first jump of a mogul run. The description of the different properties of the cue word "Forward" led us to propose three effects: 1) the cue word brings out a language function within a motor activity, 2) the cue word supports the deployment of the different possible actions and carry out the choice of the right action, 3) the cue word allows live feedback on the action. The discussion in this article shows how the effects of the cue word do not exist per se, they exist through the dialectical relationship between the athlete and the word, and are the product of a development.